Guidelines for a University Short Course on Human-Computer Interaction - Maguire, Martin (Human-Computer Interaction. User Interface Design, Development and Multimodality, 2017)
This paper presents experience in running HCI short course as part of an Ergonomics Masters programme. It comprises of a series of lectures, and practical exercises to develop the skills and knowledge required for undertaking interaction design work and usability and UX evaluation. These cover the psychology underlying human-computer interaction and user experience, user-centred design process (UCD), user research, prototyping, user testing, control of systems, information architecture, persona and scenario based design techniques, user interface design, usability testing, and HCI in certain application areas. The course tries to adopt best practice based on constructivist learning and Bloom’s taxonomy where students can relate the teaching to their own experiences and are guided through a UCD process starting with research and creating an application. A SWOT analysis highlights some key areas where the course can improve if it is to keep up with learning techniques and technologies and to become efficient in a world where University courses are becoming more expensive. Opportunities for the future of the course are to learn more technical tools for prototyping, breaking out of the classroom to interact with people in the real world, and better integration of all presentations to create providing a stronger unifying HCI theme. Guidelines are offered for organisers of similar courses in the future.